2016
DOI: 10.1128/jcm.01376-16
|View full text |Cite
|
Sign up to set email alerts
|

Culture of Urine Specimens by Use of chromID CPS Elite Medium Can Expedite Escherichia coli Identification and Reduce Hands-On Time in the Clinical Laboratory

Abstract: Urine is one of the most common specimen types submitted to the clinical microbiology laboratory; the use of chromogenic agar is one method by which the laboratory might expedite culture results and reduce hands-on time and materials required for urine culture analysis. The objective of our study was to compare chromID CPS Elite (bioMérieux), a chromogenic medium, to conventional primary culture medium for evaluation of urine specimens. Remnant urine specimens (n ‫؍‬ 200) were inoculated into conventional medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Other studies have looked at the effects on TAT for CPSE agar using only manual reading and reporting. One study evaluated 200 urine specimens using the CPSE agar and found that the time to ID for E. coli was significantly reduced (2.7-h reduction) in a comparison of bacterial culture on blood agar and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for identification (21). The study also evaluated hands-on time and consumable usage and found that CPSE agar required 30 s less hands on time (on average) and used 1 less swab and biochemical test per specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have looked at the effects on TAT for CPSE agar using only manual reading and reporting. One study evaluated 200 urine specimens using the CPSE agar and found that the time to ID for E. coli was significantly reduced (2.7-h reduction) in a comparison of bacterial culture on blood agar and matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) for identification (21). The study also evaluated hands-on time and consumable usage and found that CPSE agar required 30 s less hands on time (on average) and used 1 less swab and biochemical test per specimen.…”
Section: Discussionmentioning
confidence: 99%
“…Enteroccocal growth was inhibited in three of the five tested media (UTI C, BMagar and Microbiology laboratories always attempt to reduce the turnaround time and the cost of pathogens identification and their susceptibility testing (Strauss and Bourbeau, 2015). In recent years, chromogenic culture media have been widely used in clinical microbial diagnostic for detection and preliminary identification of pathogens and antimicrobial resistance mechanisms (Fillius et al, 2003;Kuch et al, 2009;Stefaniuk et al, 2016a;Yarbrough et al, 2016). In our study, apart from the results obtained using the three chromogenic media used all over the world (CPSE, ORI and UTI C), we present results obtained using two media manufactured in Poland: BMagar -BioMaxima and ORIE -Graso, which are offered for a lower price.…”
Section: Number Of Isolates (N)mentioning
confidence: 99%
“…The pathogen identification is based on chromogenic substrates contained in the media to detect the bacterial enzymes, mainly β-galactosidase, β-glucosidase, β-glucuronidase (the bacteria grow in the form of pink-red or blue-green colo nies, respectively) and tryptophan deaminase, which is characteristic for the Proteae group of bacteria (Proteus-Morganella-Providencia). These pathogens appear on chromogenic media as brownish colonies (Fallon et al, 2003;Pezzlo, 2014;Yarbrough et al, 2016).…”
mentioning
confidence: 99%
“…It also failed to identify two isolates of Enterobacter spp. Their final identification required additional biochemical reactions ( 31 ). Inability to identify Citrobacter, Burkholderia, Acinetobacter, Group B Streptococcus and Enterobacter were not included as major errors as this media does not reliably detect them.…”
Section: Discussionmentioning
confidence: 99%